1993
DOI: 10.1136/bjo.77.10.642
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic features and visual prognosis in the Treacher-Collins syndrome.

Abstract: (BrJ Ophthalmol 1993; 77: 642-645)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 14 publications
0
33
0
4
Order By: Relevance
“…71 In addition, strabismus, vision loss, and amblyopia are common. 76,77 Mandibular hypoplasia often presents as Pierre Robin sequence. 71 The combined effect of mandibular and maxillary hypoplasia often leads to significant ankylosis of the temporomandibular joint.…”
Section: Treacher Collins Syndromementioning
confidence: 99%
“…71 In addition, strabismus, vision loss, and amblyopia are common. 76,77 Mandibular hypoplasia often presents as Pierre Robin sequence. 71 The combined effect of mandibular and maxillary hypoplasia often leads to significant ankylosis of the temporomandibular joint.…”
Section: Treacher Collins Syndromementioning
confidence: 99%
“…In that study exotropia was more common than esodeviations, though various other studies have shown the incidence of esodeviations compared to exodeviations to be roughly equal. 15,14 In our study, 5.29% of the patients with gaze abnormalities had esotropia and 16.55% of the patients had exotropia. 11.26% of orthophoric gaze patients had nystagmus.…”
Section: Resultsmentioning
confidence: 88%
“…As alterações mais frequentes são: estrabismo, ametropias e alterações palpebrais, dentre outras (33,34).…”
Section: Discussionunclassified